2021
DOI: 10.3390/vaccines9121486
|View full text |Cite
|
Sign up to set email alerts
|

Immune Thrombocytopenia Induced by the Chimpanzee Adenovirus-Vectored Vaccine against SARS-CoV-2 Infection

Abstract: We present a case of immune thrombocytopenia (ITP) induced by the chimpanzee adenovirus-vectored vaccine, without evidence of thrombosis, eight days after vaccine administration. The thrombocytopenia condition improved after administering steroid treatment. This adenovirus vaccine had been reported to induce rare side effects, such as immune thrombotic thrombocytopenia. This case report showed that it could also induce immune thrombocytopenia without the presence of thrombosis. Therefore, we should be cautious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Considering platelet-autoantibodies have been found in both adenoviral vector and mRNA COVID-19 vaccine recipients [ 21 , 22 , 23 ], but not healthy individuals [ 8 , 24 ], we examined the association between the (type of) vaccine(s) and the presence of platelet-autoantibodies. We found that the risk of developing antibodies was independent of the (type of) vaccine and we therefore concluded there is no association between the (type of) vaccine or the presence of platelet-antibodies in clinically suspected VITT patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considering platelet-autoantibodies have been found in both adenoviral vector and mRNA COVID-19 vaccine recipients [ 21 , 22 , 23 ], but not healthy individuals [ 8 , 24 ], we examined the association between the (type of) vaccine(s) and the presence of platelet-autoantibodies. We found that the risk of developing antibodies was independent of the (type of) vaccine and we therefore concluded there is no association between the (type of) vaccine or the presence of platelet-antibodies in clinically suspected VITT patients.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of vaccine-related ITP usually has a time relationship, occurring mainly within 42 days after vaccination [5] . Since the beginning of the COVID-19 mass immunization campaign, several case-reports or case-series of ITP following vaccination have been described in the literature [5] , [6] , [7] , [8] . In some cases, underlying autoimmune medical conditions may have contributed to the ITP occurrence but it appears infrequent [8] .…”
Section: Discussionmentioning
confidence: 99%